Development Of Digital Storybook Teaching Materials for Pancasila Education Learning on the Topic of My Country Indonesia for 4th-grade Elementary School Students - Hati, Putri Arum Laras; Setyawan, Agung; Novitasari, Neni (eductum: Jurnal Literasi Pendidikan, 2024)
The purpose of this development research is (1) to develop a teaching materials digital storybook for Pancasila Education learning on the topic of My Country Indonesia for 4th-grade elementary school students that are valid, as assessed by expert validation; (2) to develop a teaching materials digital storybook for Pancasila Education learning on the topic of My Country Indonesia for 4th-grade elementary school students that are effectively implemented, as assessed by hypothesis testing using the t-test; and (3) to develop digital storybook teaching materials for Pancasila Education learning on the topic of My Country Indonesia for 4th-grade elementary school students that are practical, as assessed by the results of teacher and student practicality questionnaires. The research development method is the Research and Development (R&D) model ADDIE. The research subjects are 27 fourth-grade students from SDN Karangan 2. Obtained results: language validation 0.9, material validation 0.73, design validation 0.87, and learning design validation 0.77, indicating that the digital storybook teaching materials are valid. The hypothesis testing result showed 0.000 ≤ 0.05 (there is a difference in learning outcomes after the application of the digital storybook teaching material), thus the teaching material is considered effective. The practicality results show that the storybook teaching materials are practical for use, with a percentage of 80% deemed practical by teachers and a percentage of 88% deemed practical by students. The digital storybook teaching material was developed as a support in the Pancasila Education learning on the topic "My Country Indonesia" for the fourth-grade students of elementary school.